Splinted and unsplinted overdenture attachment systems: A systematic review and meta-analysis - Leão, R. S.; Moraes, S. L.D.; Vasconcelos, B. C.E.; Lemos, C. A.A. [UNESP]; Pellizzer, E. P. [UNESP] (Wiley, 2018)
Splinted and unsplinted overdenture attachment systems have unique advantages and disadvantages. The aim of the present systematic review was to determine the influence of splinted and unsplinted overdenture attachment systems on the marginal bone loss, prosthetic complications and implant survival rate. PubMed/MEDLINE, Scopus and Cochrane databases were searched for articles published up to October 2017, using the following search terms: “overdenture AND attachment OR overdenture AND bar OR overdenture splinted.” The PICO question “Do splinted overdenture attachment systems promote better clinical results in comparison to unsplinted systems?” was evaluated. Eligible studies included randomized controlled clinical trials, prospective studies with at least 10 participants and a minimum follow-up of 6 months, and studies published in English that compared splinted and unsplinted attachment systems within the same study. The 95% confidence interval (CI) was considered for all outcomes analysed. After completion of the different steps in the article selection process, nine articles were included in the qualitative and quantitative analyses. A total of 984 implants were placed in 380 patients (mean age: 62.8 years). The meta-analysis demonstrated no statistically significant differences between splinted and unsplinted attachment systems with regard to marginal bone loss (P =.39; MD: −0.11; 95% CI: −0.37 to 0.14), complications (P =.31; RR: 1.26; CI: 0.80-1.99) and implant survival rate (P =.14; RR: 0.37% CI: 0.10-1.36). In addition, splinted and unsplinted overdenture attachment systems achieved similar results with regard to marginal bone loss, prosthetic complications and implant survival rate.
Keywords: bone resorption; complications; dental implant; denture precision attachment; overdenture; systematic review